Islamic Education Renewal K.H. Hasyim Asy'ari: Indonesian Muslim Intellectual Figure of XX Century - Sofirah Sofirah (Universitas Muhammadiyah Enrekang, 2023)
The degree of necessity and ingenuity shown by Indonesia's authorities and the Muslim community, which serves as its principal backer, is what essentially determines how contemporary Islamic education in that country is. In order to satisfy the requirements and expectations of the Islamic community in the area of Education in the current period, the flexible and dynamic structure of the Islamic educational institution system enables it to continue to expand and adapt to its living environment. Throughout the early 20th century, several experiments—conducted by both people and organizations—have been made with this end in mind. How can they incorporate modernism while keeping Islamic education true to its roots? Investigate KH's educational reform's concepts and initiatives to that goal. Hashim Asy'ari had a significant role in the growth of madrassas in the nation. It was determined using a descriptive-analytical technique that Hashim's dedication to his renewal efforts while adhering to tradition in a wide sense led to a new structure of Islamic Education, which helped create a solid basis for the modernity of Indonesian Islamic Education. The most significant contribution made by K.H. Hasyim was his ability to combine elements of modernity and tradition of Islamic education while maintaining